Place et rôle des interactions entre élèves en classe : une spécificité affirmée en EPS - Lucie Mougenot (Éducation et Socialisation)
In the school context, the articulation between the transmission of disciplinary contents and educational aims is a major issue, all the more so as the school is increasingly solicited for its role in the socialization of students. This article highlights the representations that teachers have of socialization in and through school and of their own role in this respect. More specifically, we question the pedagogical specificity that PE teachers can bring in comparison to their colleagues of other disciplines of the secondary level, because the body play and the support on numerous collective practices tend to multiply the interactions between peers and to favour the construction of the relationship with others. This exploratory study, conducted by means of interviews, brings to light differences in the place and role of interactions according to the teachers and the disciplines.